Copying Geological Relics in the Process of Preservation and Restoration of Architectural Monuments - Stasyuk, Оlena; Dziubanovska, Tetiana (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
Lviv is a historic city known for its architectural landmarks. The historic part of Lviv, which is included in the UNESCO World Heritage List, has the majority of its buildings constructed from stone. This architecture – walls, towers, townhouses on Rynok Square, sacred structures, and so on – requires preservation, constant care, and often restoration. For professional and thorough restoration of stone objects, it is essential to understand the nature of the material from which the monument was built. Here, collaboration with the Faculty of Geology at Lviv University provides invaluable support. Professors and geology students study the geological material from which Lviv was built, including its precise dating and origin. Such information is particularly valuable when it is necessary to supplement damaged details or replicate lost ones. At the same time, during such detailed study of geological materials on Lviv’s streets, geology students discover fossils or remnants of ancient organisms, which are valuable scientific objects. Most often, these are various shells, and sometimes plant leaves. A true gem discovered on a stone in a street curb at 6 Akademika Hnatyuka Street in Lviv is a fossil of a starfish. This unique and extraordinary geological relic undoubtedly deserves preservation. Simultaneously, this geological relic is part of the city’s street, meaning it is part of its architecture, and currently cannot be removed. As part of the collaboration between Lviv University and Polytechnic University, involving the Department of Geology and the Department of Architecture and Restoration, a mold was taken from the relic, and subsequently, a replica of the starfish fossil was created. Today, the object is housed in the university’s geological museum and is one of its valuable exhibits. This article analyzes the methodology for copying geological relics and presents the step-by-step process of creating a copy of such a relic, using the example of the starfish from Lviv.